(untitled) (General Practice, 2026)
Introduction. Continuous Medical Education (CME) represents a cornerstone of professional development for healthcare workers. It enables the ongoing enhancement of knowledge and skills while ensuring alignment with the latest scientific research and technological advancements. Modern approaches to CME emphasize the design of programs that are compatible with the evolving needs of health professionals and responsive to the health demands of the population. Objective. We aimed to examine the level of satisfaction and motivation among health workers in participating in CME programs, to identify their principal shortcomings, and to analyze their impact on professional development as well as on the sustainability of the health system. Method. First, we defined the basic concepts related to CME in Serbia, including its organization, accreditation, and the process of program validation. We then conducted an empirical cross-sectional study to assess the satisfaction and motivation of health workers in Primary Healthcare Center Krusevac and General Hospital Krusevac regarding their participation in CME programs. Results. Our research revealed a predominance of female respondents (85.7%), who also demonstrated greater willingness to participate in the survey. In terms of age distribution, the 40–49 age group was most represented (41.6%). The most common length of work experience was between 10 and 20 years (42.9%), indicating that the sample consisted of participants with substantial professional experience. The majority of respondents were nurses/technicians (62.3%), while physicians accounted for 23.4%. Conclusion. Continuous Medical Education (CME) is a key factor in the professional development of health workers and in enhancing the overall quality of healthcare. Our findings highlight the need for further improvement and for strengthening motivation to participate in CME programs. Ongoing advancement in this area is essential to ensure the sustainability of the health system and the delivery of high-quality patient care.